2019
DOI: 10.3390/medicina55110741
|View full text |Cite
|
Sign up to set email alerts
|

Affective and Substance Abuse Disorders Following Abortion by Pregnancy Intention in the United States: A Longitudinal Cohort Study

Abstract: Background and Objectives: Psychological outcomes following termination of wanted pregnancies have not previously been studied. Does excluding such abortions affect estimates of psychological distress following abortion? To address this question this study examines long-term psychological outcomes by pregnancy intention (wanted or unwanted) following induced abortion relative to childbirth in the United States. Materials and Methods: Panel data on a nationally-representative cohort of 3935 ever-pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…Ideally, more prospective longitudinal studies should be undertaken which include data on prior mental health, pregnancy intention, and other confounding factors years prior to the participants’ first pregnancies. Unfortunately, while a few high quality prospective studies have been done, the underlying data gathered for these studies was general in nature: The questionnaires were not designed to focus on research questions specific to the abortion experience [ 8 , 20 , 37 ]. Therefore, we recommend that new and existing national prospective survey designs should include input from experts on both sides of the abortion and mental health controversy to ensure better that the most useful questions are included.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, more prospective longitudinal studies should be undertaken which include data on prior mental health, pregnancy intention, and other confounding factors years prior to the participants’ first pregnancies. Unfortunately, while a few high quality prospective studies have been done, the underlying data gathered for these studies was general in nature: The questionnaires were not designed to focus on research questions specific to the abortion experience [ 8 , 20 , 37 ]. Therefore, we recommend that new and existing national prospective survey designs should include input from experts on both sides of the abortion and mental health controversy to ensure better that the most useful questions are included.…”
Section: Discussionmentioning
confidence: 99%
“…The Danish researchers' conclusions have also been called into question by both prior studies which employed better methodologies, [3,4] and subsequent studies. [11][12][13][14] For example, an analysis of the National Longitudinal Study of Adolescent to Adult Health (Add Health) which controlled 25 confounding factors, including prior mental health and exposure to violence, found that each exposure to abortion increased the risk of subsequent mental health disorders, a finding that could not be explained by prior mental health. [11] In addition, the subset of women who reported aborting a wanted child experienced a 122% higher rate of depression and a 244% higher rate of suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…The range of possible examples of mental health problems or issues and the means by which they can be operationalized or measured are extensive. Just a few examples to illustrate the diversity: depression scores from a questionnaire; 16 bipolar disorder and unplanned or interrupted pregnancies; 17 past adverse pregnancy outcome (stillbirth, abortion, or a child’s death) associated with depression; 18 insomnia, anorexia and severe depression requiring hospitalization following therapeutic abortion; 19 clinical psychologist assessment of depression within one week of chemical or surgical abortion; 20 alcohol, tranquilizer and other substance abuse related to abortion; 21 substance abuse and suicide rates following termination of unwanted versus wanted pregnancies; 22 National Comorbidity Survey, history of abortion and substance abuse disorder; 23 detoxification center patients and prior abortions; 24 history of abortion and smoking and drinking during pregnancy; 25 and drug overdose both before and after abortion. 26 This very small sample of studies suggests the need for some more comprehensive measure of overall mental health service utilization which can be applied to population denominators.…”
Section: Introductionmentioning
confidence: 99%